The impact of internet penetration on corporate income tax filing in South Africa - Collen Lediga (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
Tax administrations around the world have introduced e-filing of tax returns due to its potential to improve tax return filing compliance. The introduction of this service for businesses in South Africa has not yielded the expected results. Drawing on tax administrative data on tax return filing and population census data, the study aims at determining whether internet access in the country, could have contributed to the less impact of the introduced administrative intervention. Accounting for specific characteristics of the areas in the country, and geoclassication (urban or rural area), we find that an increase in the fraction of household areas with internet access by 10 percentage points, raises the fraction of businesses that do submit a tax return by 1.86 percentage points. The results of the analysis highlights that the impact of the introduction of e-filing services for tax returns submission, is dependent on the internet coverage of the area. – – Steuerverwaltungen auf der ganzen Welt haben die elektronische Abgabe der Steuererklärung eingeführt, da dies die Anzahl der abgegebenen Erklärungen verbessern kann. Die Einführung dieser Serviceleistung für Unternehmen in Südafrika hat jedoch nicht zu den erwarteten Ergebnissen geführt. Auf der Grundlage von Daten der Steuerverwaltung zur Abgabe von Steuererklärungen und von Daten der Volkszählung analysiert diese Studie, ob die Internetverfügbarkeit im Land zu dem geringen Effekt der eingeführten administrativen Intervention beigetragen haben könnte. Unter Berücksichtigung der spezifischen Merkmale verschiedener Regionen im Land und der geografischen Einteilung (städtische oder ländliche Gebiete) stellen wir fest, dass eine Erhöhung des Anteils der Haushaltsgebiete mit Internetzugang um 10 Prozentpunkte den Anteil der Unternehmen, die eine Steuererklärung abgeben, um 1,86 Prozentpunkte erhöht. Die Ergebnisse der Analyse machen deutlich, dass die Auswirkungen der Einführung der elektronischen Abgabe der Steuererklärung von der Internetabdeckung der jeweiligen Region abhängen.
Keywords: H2; H7; 330; corporate taxation; e-filing; less developed countries; tax administration